Biodegradable zein-based blend films: Structural, mechanical and barrier properties - Pena-Serna, Carolina [UNESP]; Lopes Filho, José Francisco [UNESP] (My University, 2015)
The effect of adding a hydrocolloid on the structural, mechanical and barrier properties of zein-based blend films is evaluated. Zein-oleic acid blend film with added xanthan gum (Z-OA-XG) showed higher water solubility (13.09 %) and opacity (8.49 AU/mm) than zein-oleic acid (Z-OA) film (10.80 % and 5.19 AU/mm, respectively). Furthermore, Z-OA film had greater flexibility with lower Young's Modulus (YM=5.02 MPa) and higher elongation at break (η=10.62 %); nonetheless, it was less resistant to tension (tensile strength s=8.5 MPa) than Z-OA-XG film, which showed YM, η and s of 6.38 MPa, 6.66 % and 10.485 MPa, respectively. Both films had glossy and homogeneous structure with comparable water vapour and oxygen barrier properties around 4.39·10-11 and 1.82·10-13 g/(Pa·s·m), respectively. Based on that, xanthan gum structure influenced mainly mechanical and light barrier properties of zein-oleic acid blend films.
Keywords: Biodegradable material; Blend film; Microstructure; Permeability; Tensile properties